Perbandingan Tiga Metode Axiolateral Petromastoid Untuk Visualisasi Anatomi Informatif - Mareta, Santa; Nangsih, Livia Ade; Hanifah, Wahdini; Pratama, Dimas Anugrah (Lontara Journal of Health Science and Technology, 2025)
Petromastoid examination often shows results that are not in accordance with theory due to variations in examination techniques carried out using several different axiolateral projection methods. This study aims to compare three axiolateral projection radiography methods, namely the Henschen, Schuller, and Lysholm methods, in order to determine which method produces the most informative and high-quality images of petromastoid anatomy. quantitative type with an experimental design, carried out at Padang Pariaman Regional Hospital from June-July 2024 involving three patient samples using a purposive sampling method, as well as five radiology specialist doctors as respondents to fill out the questionnaire. Data processing was carried out using the Friedman statistical test shown in the table. The results showed that the Schuller method, with an angle of 25°, provided the clearest and most complete picture of the petromastoid anatomy with a mean value (2.325) compared to the Henschen and Lysholm methods which was the highest in 1 showing the mastoid antrum, MAE, mastoid process and mastoid air cavity compared to the Henschen method (1.525) and the Lysholm method (2.175). In addition, this method is considered superior in terms of patient comfort and ease of producing informative anatomical images. Based on these results, the Schuller method was identified as the most optimal method for examining the petromastoid, both for diagnostic purposes and improving the quality.